Surface properties and antimicrobial performance of copper coatings electrodeposited on 304 stainless steel / Nik Norziehana Che Isa - Che Isa, Nik Norziehana (Institute of Graduate Studies, UiTM, 2018)
Bacterial contamination resulted from frequently-touched surface materials is responsible in the acquisition of infection especially in hospital. The utilization of copper as antimicrobial touch surfaces offers a solution that can serve as an additional line of defense against pathogens. Copper is the first and currently the only one surface metal that has received registration from Environmental Protection Agency (EPA) as antimicrobial material which is capable to inhibit biofilms, retains the antimicrobial activity under typical indoor conditions. In this study, electrodeposition technique was used to coat copper on 304 stainless steel using 0.01 M Cu2+ solutions containing either uncomplexed CuS04 or complexed Cu-EDTA based systems. Effects of applied potential (based on CV analysis) and deposition time were investigated to study the formation, nucleation and growth of copper on the 304 stainless steel. Copper coatings Cu/SS(-0.25 V, CuS04 pH 1, 900 s) and Cu/ SS(-1.1 V, Cu-EDTA pH 8, 900 s) prepared at low overpotential from both electrolyte solutions possess good physicochemical and surface properties. In addition, they also have high contact angle,high surface roughness and well-adhered to the substrate…